Half a century of research on Bothrops asper venom variation: biological and biomedical implications. (1st January 2023) - Mora-Obando, Diana; Lomonte, Bruno; Pla, Davinia; Guerrero-Vargas, Jimmy Alexander; Ayerbe-González, Santiago; Gutiérrez, José María; Sasa, Mahmood; Calvete, Juan J.
Abstract: Snake venoms are a complex biological mixture of proteins with or without enzymatic activity, peptides, and nucleotides, among other components. It is produced in specialized secretory glands located in the maxillary region, being the result of millions of years of evolution and whose biological functions are defense, immobilization, and digestion of prey. Venoms present intraspecific (i.e., individual, ontogenetic, geographical) and interspecific (i.e., between sympatric and allopatric species) variation, and the study of this variability has become the focus of toxinological research. Bothrops asper is responsible for highest incidence, morbimortality and severe cases of envenoming in Mesoamerica and northern South America. Given its clinical importance, its venom has been characterized and compared qualitatively and quantitatively across the species range. More than 50 years of research show that B. asper venom is endowed with an interesting intraspecific variability. Knowing this variation has allowed advances in the elucidation of the biological role of the venom, a better understanding of the clinical signs and symptoms in patients envenomed by B asper, the immunological implications in the context of antivenoms production, and the generation of new ideas that could be useful to solve different biological and evolutionary questions of one of the venomous snakes with the greatest distribution and strongest public health impact in Latin America. Graphical abstract: Image 1 Highlights: Overview of recent and pioneering research on B. asper venom variation. Understanding of biological and clinical aspects of B. asper by venomics studies. Formulation of new and interesting questions about this venom in future research.